Understanding Automated Financial Trading Using Work Domain Analysis. (September 2015) - Li, Yeti; Burns, Catherine; Hu, Rui
Finance is a complex domain largely unexplored in the human factors literature. Modern financial trading systems involve a variety of coupled socio-technical systems (e.g. humans and technologies) and have become highly automated. Recent stock market crashes, such as the well-known Flash Crash, show automation-initiated dynamics. This suggests that a human factors understanding of this environment may be useful. In this article, we report an initial attempt to model buyer-side Automated Trading (AT) systems using a Cognitive Work Analysis (CWA) approach. A Work Domain Analysis (WDA) model is presented to describe the automated financial trading domain. This work has implications for applying CWA to finance but also advances the understanding of how to model a highly automated domain.